Three-dimensional quantification of soil hydraulic properties using X-ray computed tomography and image-based modeling - Tracy, Saoirse R.; Daly, Keith R.; Sturrock, Craig J.; Crout, Neil M.J.; Mooney, Sacha J.; Roose, Tiina (American Geophysical Union, 2015)
We demonstrate the application of a high-resolution X-ray Computed Tomography (CT) method to quantify water distribution in soil pores under successive reductive drying. We focus on the wet end of the water release characteristic (WRC) (0 to −75 kPa) to investigate changes in soil water distribution in contrasting soil textures (sand and clay) and structures (sieved and field structured) and to determine the impact of soil structure on hydraulic behavior. The 3-D structure of each soil was obtained from the CT images (at a 10 μm resolution). Stokes equations for flow were solved computationally for each measured structure to estimate hydraulic conductivity. The simulated values obtained compared extremely well with the measured saturated hydraulic conductivity values. By considering different sample sizes we were able to identify the smallest possible representative sample size which is required to determine a globally valid hydraulic conductivity.